Searching for the source: Extraovarian primary peritoneal carcinoma presenting as chest wall masses - Madison Brinker Feng; Nora Badiner; Linda Hong; Yevgeniya Ioffe (Elsevier, 2023)
Background: Extraovarian primary peritoneal carcinoma (EOPPC) is a rare form of epithelial adenocarcinoma arising from the peritoneal lining with little to no ovarian involvement. To date, very few cases of EOPPC with primary tumors outside of the peritoneum have been described, the majority of which present with a primary tumor in the retroperitoneum. No cases have been reported with primary presentation as a chest wall mass. Case report: This case describes a 64-year-old woman referred for the evaluation of PAX8 positive chest wall masses. Biopsies of these masses demonstrated tumor architecture that was predominantly micropapillary with rare psammomatous calcifications. Immunohistochemically, the tumor was PAX8, CK7, ER, MOC31, and BerEP4 positive, with a mutational pattern of p53. This was consistent with Mullerian adenocarcinoma markers and suggestive of high-grade serous carcinoma. The patient was diagnosed with a unique presentation of EOPPC and is currently alive at 36 months post initial diagnosis. She has been treated with a combination of diagnostic surgery, chemotherapy and radiation therapy. Conclusion: To the best of our knowledge, this is the first documented case of EOPPC presenting with a primary tumor of the chest wall. This case highlights the importance of pathology, immunohistology, and interdisciplinary collaboration in diagnosing and treating rare malignancies.